Halit Ziya Uşaklıgil’in romanlarında İstanbul - Kıyak, Hüseyin (My University, 2014)
Türk edebiyatının ilk realist romancılarından olan Halit Ziya Uşaklıgil’in başarısında mekân kullanımının payı büyüktür. Mekân ve insan arasındaki varoluşsal ve duygusal ilişkiyi ele alan yazar, mekânı, insanı şekillendiren ve insan davranışlarına yön veren bir unsur olarak işler. Yazar, İstanbul’u, roman kahramanlarının sosyal çevresi olarak görür, karakter yaratmada şehrin rolünü vurgular. İstanbul, her roman kahramanı için farklı anlamlar taşır. Şahısların şehirle kurdukları ilişkide belirleyici faktör, gelir düzeyidir. Zengin-fakir tezadı şehir üzerinden pekiştirilir ve romanın çatışma unsurunu yaratır. İstanbul onun romanlarında, ikamet edilen semtler ve meskenler, köprü, meydanlar, caddeler ve sokaklar, taşıtlar, alışveriş yerleri, eğlence yerleri, kurumlar, matbuat hayatı, tarihî yapılar ve mezarlıklar olarak yer alır. Yazar tüm bu unsurları insanla birlikte çizer. Şehre ait unsurlar kahramanların çevresini oluşturmak için kullanılır. Bunların dışında Batılı oryantalistlerin yarattıkları İstanbul imajına karşı çıkış vardır. Son romanı Nesl-i Ahîr’de şehirdeki İstibdat yönetimini de ele alır. Yazarın şehre ait bazı biyografik özellikleri de romanlarına yansımıştır. Ayrıca romanlarda, 19. yüzyıl sonu ile 20. yüzyılın başındaki İstanbul’a dair görünümler, hayatsahneleri ve diğer unsurlar yer alır. Yazar, bu bakımdan şehir tarihi için kaynak hükmünde değerlendirilebilecek romanların sahibidir. Anahtar Sözcükler: Halit Ziya Uşaklıgil, roman, mekân, şehir, İstanbul

The use of places has a great importance in the success of Halit Ziya Uşaklıgil, one of the first realist novelists of Turkish literature. The writer, dealing with the existential and sentimental relationship between human and place, describes the place as a factor shaping the human and directing his behaviour. He considers İstanbul as the characters’ social environment and emphasizes the role of the city in creating a character. İstanbul has a different meaning for each of them. The distinctive factor of the relationship between characters and the city is the level of income. The contrast between the rich and poor is supported by the city and that creates the conflict of the novel. In his novels, İstanbul takes place as residences, neighbourhoods, bridge, squares, avenues, streets, vehicles, bazaars and shopping places, entertainment centres, institutions, the press, historical places and cemeteries. He portrays all these elements together with human. The elements of the city are used to create the surrounding of the characters. Besides these, there is an opposition to the image of Istanbul created by the western orientalists. In his last novel, Nesl-i Ahîr, he also discusses the autocracy in the city. Some biographic features of the author about the city are reflected in ABSTRACT The use of places has a great importance in the success of Halit Ziya Uşaklıgil, one of the first realist novelists of Turkish literature. The writer, dealing with the existential and sentimental relationship between human and place, describes the place as a factor shaping the human and directing his behaviour. He considers İstanbul as the characters’ social environment and emphasizes the role of the city in creating a character. İstanbul has a different meaning for each of them. The distinctive factor of the relationship between characters and the city is the level of income. The contrast between the rich and poor is supported by the city and that creates the conflict of the novel. In his novels, İstanbul takes place as residences, neighbourhoods, bridge, squares, avenues, streets, vehicles, bazaars and shopping places, entertainment centres, institutions, the press, historical places and cemeteries. He portrays all these elements together with human. The elements of the city are used to create the surrounding of the characters. Besides these, there is an opposition to the image of Istanbul created by the western orientalists. In his last novel, Nesl-i Ahîr, he also discusses the autocracy in the city. Some biographic features of the author about the city are reflected in
Keywords: 20. yy; Eserleri; Halit Ziya Uşaklıgill; İncele; İnceleme; İstanbul; Mekân; Roman; Şehir; Tarih; Türk Edebiyatı